Культура браслетов в поздней преистории Европы (дунайская линия развития) - Манзура, И.В.; Орлова, Т.А. (Материалы по археологии Северного Причерноморья, 2010)
The article is devoted to the spatial and temporal analysis of bracelets in the later prehistory of Europe (the Neolithic and Copper Age). The finds are considered across four large regions: West, Central and Southeast Europe as well as the southern part of East Europe. Additionally, they are studied within four chronological periods: the Early and Late Neolithic (6300–5100/5000 BC) and the Early and Late Copper Age (5100/5000–3500 BC). The study includes about 3500 bracelets and their fragments made of stone, shell, fired clay, bone, copper and gold which come from 733 localities. About 3300 objects are related to 533 archaeological sites with determined cultural and chronological position. All items are organized within a data base (Appendixes 1–6) which contains information about their chronological and cultural attribution, archaeological context (settlements, burials, hoards and stray finds) and sources. Only bracelets with clear chronological position are mapped (Maps 1–9).